Combining haptic guidance and haptic disturbance: an initial study of hybrid haptic assistance for virtual steering task - Hojin Lee; Seungmoon Choi (IEEE Haptics Symposium, 2014)
In this paper, we present an experimental study in which we tested the feasibility of a hybrid haptic assistance scheme that combines haptic guidance and disturbance. In our hybrid method, haptic guidance is used in the initial phase of learning, but it is progressively turned into haptic disturbance as the learner's performance improves. The purpose of haptic guidance is to help learners become familiar with a new motor skill more quickly and easily, while the use of haptic disturbance is to further improve the learners' skill in the later stage of training. In order to assess the performance of hybrid haptic assistance, we conducted a human subjects experiment using a virtual steering task along with three other methods of no assistance, progressive haptic guidance, and haptic disturbance. Experimental results indicated some advantages of hybrid haptic assistance and progressive haptic guidance for the steering skill, but did not show any statistically significant differences in terms of absolute tracking errors among the four methods in both immediate and delayed retention test. However, further analysis provided more insights for the effects of different haptic assistance methods on two classes of skills (open-loop road tracking and closed-loop error canceling) required for our experimental task, which may offer some new ideas for future research.